2022
DOI: 10.4102/hsag.v27i0.1968
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ perception on their readiness to combat gender-based violence during the COVID-19 pandemic

Abstract: Background: Gender-based violence (GBV) is a critical public health concern, demanding for global coordinated efforts. While nursing students form part of a healthcare team with significant roles in identifying and responding to abused victims, studies assessing their readiness to combat GBV are limited in Namibia.Aim: To assess undergraduate nursing students’ perceptions and to determine the relationship of the study variables to readiness to combat GBV during the coronavirus disease 2019 (COVID-19) pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The ADKAR model is a Prosci Methodology model that researchers have successfully applied in various fields, such as education, 17 business, 18 information technology, 13 and healthcare. 14 We selected ADKAR model for its reliability, validity, and alignment with our study aim. We measured the 5 dimensions of the ADKAR model using 22 questions that participants answered on a 5-point Likert scale from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ADKAR model is a Prosci Methodology model that researchers have successfully applied in various fields, such as education, 17 business, 18 information technology, 13 and healthcare. 14 We selected ADKAR model for its reliability, validity, and alignment with our study aim. We measured the 5 dimensions of the ADKAR model using 22 questions that participants answered on a 5-point Likert scale from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Nestor and Gideon conducted a study to assess nursing perceptions and readiness to combat gender-based violence (GBV) during the COVID-19 pandemic in Namibia using the ADKAR model. 14 The results indicated that the readiness was highest in the reinforcement and awareness dimensions with gender and age were significant predictors of readiness. 14 Moreover, Alice et al.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations